Effects of smartphone-based chatbot intervention to increase influenza and COVID-19 vaccine uptake among South Asian ethnic minorities in Hong Kong: protocol for a randomised waitlist-controlled trial - Kai Chow Choi; Cho Lee Wong; Carmen Wing Han Chan; Winnie Kwok Wei So; Huiyuan Li (BMJ Open)
Introduction Protecting non-native ethnic minority groups against cocirculation of influenza and COVID-19 is crucial, and vaccination could be a viable option. Smartphone-based chatbots offer promising opportunities for improving vaccine knowledge and addressing barriers encountered by ethnic minorities. This trial aims to evaluate the effects of smartphone-based chatbot intervention on influenza and COVID-19 vaccine uptake, intention to receive vaccination and vaccine hesitancy among South Asian ethnic minorities in Hong Kong.Method and analysis An assessor-blinded, cluster-randomised, waitlist-controlled trial will be conducted. This study consists of two phases. In phase I, a smartphone-based chatbot intervention will be developed, including designing a simple chatbot called ‘Ali’ to deliver prewritten educational text messages and vaccination reminders as well as respond to users’ questions, and on-demand option for communication with research assistants. An expert panel will be invited to review the designed chatbot, and pilot testing will be performed. In phase II, a total of 612 South Asians will be recruited from each of the six participating non-governmental community centres or ethnic minority associations. They will be randomly allocated to intervention (n=306) or waitlist control group (n=306). The intervention group will receive in-app notifications related to the education text messages and vaccination reminders via the smartphone-based chatbot twice a week for two weeks. The waitlist control group will receive usual care only. Evaluation will include vaccination uptake, intention to receive vaccination and vaccine hesitancy. Assessments will take place at baseline (T0), immediately postintervention (T1) and 3-month postintervention (T2).Ethics and dissemination This study has been approved by the Joint Chinese University of Hong Kong-New Territories East Cluster Clinical Research Ethics Committee (CREC Ref. No.: 2021.688). The findings will be disseminated in peer-reviewed journals and through local or interventional conference presentations.Trial registration number ChiCTR2200061503.